Implementation of the process-oriented guided inquiry learning model to improve learning ownership, communication skills, and cognitive learning outcome - Rifdah Aristawidya; Herawati Susilo (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Entering the 21st century, education increasingly emphasizes not only academic achievement but also the development of soft skills, particularly learning ownership and communication skills as essential competencies for facing global challenges. This study aims to enhance students' learning ownership, communication skills, and cognitive learning outcomes through the implementation of the Process-Oriented Guided Inquiry Learning (POGIL) model. This study utilized a classroom action research (CAR) approach, which was carried out in two cycles, each comprising the stages of planning, implementation, observation, and reflection. The research participants included 26 students from grade XI Science 3 at one of senior high school in Malang Regency. Data were collected through observations, learning ownership questionnaires, communication skills tests, and cognitive learning outcome tests, which were then analyzed using descriptive quantitative and qualitative methods. The findings indicate that continuous implementation across the CAR cycles led to steady improvement in students’ learning ownership, communication skills, and cognitive learning outcomes. The percentage of students meeting the success indicators for these three aspects increased in the first cycle compared to the initial data, with a more significant improvement observed in the second cycle. POGIL encourages active student engagement in learning and fosters a deeper understanding of concepts. Thus, the implementation of POGIL is effective in promoting a more active and meaningful learning process, particularly in biology education.